Sourcing Olive Jars Using U‐Pb Ages of Detrital Zircons: A Study of 16th Century Olive Jars Recovered from the Solomon Islands. Issue 1 (11th December 2013) - Kelloway, Sarah J.; Craven, Steven; Pecha, Mark; Dickinson, William R.; Gibbs, Martin; Ferguson, Timothy; Glascock, Michael D.
<x xml:space="preserve">Abstract</x> We present U‐Pb ages of zircons extracted from olive jars recovered from two sites associated with Alvaro de Mendaña y Neyra's colonising expedition to the Solomon Islands, c. 1595–1596 A.D. The olive jars were previously associated with Panamanian and Peruvian origins based on petrological and geochemical studies. To further define provenance, 143 zircons were extracted from five olive jar sherds, analyzed and dated. The resultant U‐Pb ages range from the Archaean to the Cenozoic (2977.2 ± 29.0–3.2 ± 4.0 Ma), but the dominance of Cretaceous and Palaeogene ages (∼ 90% of the total age population is between ∼ 145 and 23 Ma) supports a Peruvian origin based on comparative geology, with the Coastal Batholith of Peru a prime candidate area of ceramic production. These results are significant for the characterization of 16th Century Peruvian‐made pottery and our understanding of its production and trade.